Sonographic Evaluation of Gallbladder Distension Based on Interval Fasting Hours: A Prospective Study - Mohammed Alsaadi (International Journal of Biomedicine, 2025)
The primary objective of this study was to systematically investigate the relationship between gallbladder (GB) distension and fasting duration (FD) by measuring the length and width of the gallbladder. Methods and Results: A total of 30 healthy adult male volunteers (mean age: 23 ± 0.20 years; mean BMI: 23.16 ± 1.89 kg/m²) were recruited through convenience sampling. Participants were stratified into three groups based on their FD: Group A (n=10) with FD of 8 hours, Group B (n=10) with FD of 6 hours, and Group C (n=10) with FD of 4 hours. Each participant underwent a standardized GB ultrasound scan, during which the size and characteristics of the GB were measured in both transverse and longitudinal planes. Longitudinal GB size increased significantly with FD (P=0.016): 46.84±8.83 mm (4 hours), 54.82±11.93 mm (6 hours), and 59.63±6.37 mm (8 hours). The transverse size showed no significant difference (P=0.193): 19.42±4.60 mm (4 hours), 3.48±5.35 mm (6 hours), and 22.56±5.27 mm (8 hours). GB wall thickness did not differ significantly across the three time points (P=0.766): 0.14±0.97 mm (4 hours), 0.22±0.57 mm (6 hours), and 0.42±1.03 mm (8 hours). The GB neck was visualized in 40% of cases at 4 hours and 100% at 6 and 8 hours. Cystic duct visualization showed no significant difference (P=0.585), with rates of 40%, 60%, and 60% at 4, 6, and 8 hours, respectively. Conclusion: Fasting for four hours can provide adequate GB visualization in most healthy individuals, with no significant issues evaluating the wall, cystic duct, or lumen. Prolonged fasting durations may improve the visualization of the GB neck, although they are not always necessary. Standardizing the fasting duration to four hours may optimize workflow while preserving diagnostic quality in routine practice.